PENDIDIKAN INTEGRALISTIK PERSPEKTIF HAFIDZ HASAN AL-MAS’UDI - Saeful Bahri; Tri Subhi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to answer important questions regarding Al-Mas'ūdī's thoughts on integralistic education through vertical and horizontal communication applied in moral education. The method used in this research is qualitative, the type of research is in the form of literature with a philosophical main approach. The analysis technique taken uses the comparative descriptive method. The results of his research show that, Integralistic education in the perspective of Ḥāfiẓ Ḥasan Al-Mas'ūdī contained in the work Taisīr al-Khallāq fī 'Ilmi al-Akhlāq is described in five problems: (1) the purpose of education that relies on moral education which is described integrally both vertically and horizontally, (2) educators and students whose key to success is both self-personality and harmonious relationships, (3) family education by habituating noble morals in order to interact and maintain good relations with their families, (4) community social education is carried out by raising awareness of the importance of balancing community social relations with the foundation of taqwa, (5) national education, can be applied through an exemplary approach by cultivating religious values, being fair, having a big spirit, loving the nation and its country.